ANALISIS FAKTOR YANG MEMPENGARUHI PERMINTAAN BELANJA ONLINE PADA MASYARAKAT KOTA PAKANBARU - Vinny, Marlinda; Syaril, Basri; Deny, Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted on the community in Pekanbaru City. The purpose of this study is 1) to find out whether prices have an influence on online shopping demand in the city of Pakanbaru. 2) To find out whether income has an influence on online shopping demand in the city of Pakanbaru. 3) To find out whether gender has an influence on online shopping demand in the city of Pakanbaru. The theory used in this research is the theory related to demand. The type and approach of this research is a descriptive study with a quantitative approach. The total population of this study was 1,149,359 people of Pekanbaru City. The sampling technique used is convenience sampling. The data used in this study are secondary data and primary data. Data collection was carried out by means of a questionnaire. The data analysis technique used in this study is multiple linear regression with the help of the SPSS (Statistical Product and Solution) 25 program. The results of the data analysis show that the R2 value is 0.748, meaning that price, income and gender affect online shopping demand by 74.8% whereas 25, 2% is influenced by other factors not analyzed in this study. From the results of statistical tests it can be seen that the significant value of the F test of 0,000 is smaller than 0.05. So it can be concluded that price, income and gender simultaneously or jointly affect the demand for online shopping.Keywords : Online Shopping Requests, Prices, Income and Gender